TiO2 and TiO2-Doped Films Able to Kill Bacteria by Contact: New Evidence for the Dynamics of Bacterial Inactivation in the Dark and under Light Irradiation - John Kiwi; Sami Rtimi; Rosendo Sanjines; Cesar Pulgarin (International Journal of Photoenergy)
This paper addresses recent developments in the design, evaluation, and characterization of flexible, uniform polyethylene-TiO2 (PE-TiO2), TiO2-In2O3, and TiO2-polyester able to inactivate bacteria under band gap irradiation and in the dark. The preparation of these bactericide films by sol-gel or by sputtering techniques is reported. The E. coli loss of viability kinetics under low intensity and actinic light is evaluated. Evidence for kinetics of the major steps leading to bacterial disinfection in the dark is presented by electron microscopy (TEM). The film surface properties were characterized by surface techniques like EM, DRS, XPS, ATR-IR, CA, AFM, XRD, and XRF. The surface characterization allows the correlation of the film surface morphology with the self-disinfection performance. The events taking place at the cell wall leading to bacterial inactivation when in contact with the TiO2 films are presented and the steps related to the bond stretching preceding bond scission identified by ATR-IR.